A case study of the top 100 favoured songs on Apple Music platform among Malaysians based on their song track attributes / Haziq Nazhan Hamdan - Hamdan, Haziq Nazhan (2023)
The purpose of this study was to investigate the top 100 favored songs on the Apple Music platform among Malaysians, based on their song track attributes. This study used secondary and quantitative data to analyze the popularity and song track attributes of the top 100 songs in Malaysia on the Apple Music platform. The results of this study show that the most popular songs in Malaysia are primarily influenced by American, British, Korean, Indonesian, and Canadian music, with American music being the most favored among Malaysians. Additionally, the study found that the most preferred music genre among Malaysians is Pop music, accounting for 84% of listeners on the Apple Music platform. Based on these findings, it is recommended that Malaysian artists aim to incorporate elements from popular music styles, such as high danceability and energetic music features, in their own music to increase their appeal and popularity among the local audience. This study contributes to the field of music analysis by providing valuable insights into the music preferences of Malaysians on the Apple Music platform.